Memahami dan Mencegah Perilaku Plagiarisme dalam Menulis Karya Ilmiah - Muhammad Abdan Shadiqi (Faculty of Psychology Universitas Gadjah Mada, 2019)
Plagiarism is a misconduct act and a scourge for science. Plagiarism perpetrators steal other author's work without citing the original references. Psychology is one of the most vulnerable sciences with plagiarism and must give more attention to this issue. Several types of plagiarism can be distinguished to the plagiarism motivation (intentional, unintentional, and inadvertent), how to do plagiarism (patchwriting, inappropriate paraphrasing, and summaries) and self-plagiarism (text recycling, redundant or duplicate publication, salami-slicing or data fragmentation). There are several reasons to do plagiarism, such as ease to get information via the internet, pressure on academic tasks, bad writing skill, hurry to write under pressure, lack of understanding how to rewrite the original reference, a misconception to understanding self-plagiarism, and habitual plagiarists. This article also presents steps to avoid plagiarism, such as avoiding